Ball of collusion ebook The plot to rig an election and destroy a presidency. - McCarthy, Andrew C. (Encounter Books, 2020)
The real collusion in the 2016 election was not between the Trump campaign and the Kremlin. It was between the Clinton campaign and the Obama administration. The media–Democrat "collusion narrative," which paints Donald Trump as cat's paw of Russia, is a studiously crafted illusion. Despite Clinton's commanding lead in the polls, hyper-partisan intelligence officials decided they needed an "insurance policy" against a Trump presidency. Thus was born the collusion narrative, built on an anonymously sourced "dossier," secretly underwritten by the Clinton campaign and compiled by a former British spy. Though acknowledged to be "salacious and unverified" at the FBI's highest level, the dossier was used to build a counterintelligence investigation against Trump's campaign. Miraculously, Trump won anyway. But his political opponents refused to accept the voters' decision. Their collusion narrative was now peddled relentlessly by political operatives, intelligence agents, Justice Department officials, and media ideologues—the vanguard of the "Trump Resistance." Through secret surveillance, high-level intelligence leaking, and tireless news coverage, the public was led to believe that Trump conspired with Russia to steal the election. Not one to sit passively through an onslaught, President Trump fought back in his tumultuous way. Matters came to a head when he fired his FBI director, who had given explosive House testimony suggesting the president was a criminal suspect, despite privately assuring Trump otherwise. The resulting firestorm of partisan protest cowed the Justice Department to appoint a special counsel, whose seemingly limitless investigation bedeviled the administration for two years. Yet as months passed, concrete evidence of collusion failed to materialize. Was the collusion narrative an elaborate fraud? And if so, choreographed by whom? Against media–Democrat caterwauling, a doughty group of lawmakers forced a shift in the spotlight from Trump to his investigators and accusers. This has exposed the depth of politicization within American law-enforcement and intelligence agencies. It is now clear that the institutions on which our nation depends for objective policing and clear-eyed analysis injected themselves scandalously into the divisive politics of the 2016 election. They failed to forge a new Clinton administration. Will they succeed in bringing down President Trump?